Principles of corporate finance - Brealey, Richard A.; Stewart C. Myers (New York : McGraw-Hill, 1996)
The book is about financial decisions by corporations. It describes the theory and practice of corporate finance, how to use financial theory to solve practical problems and also to illuminate the facts and institutional material that students of corporate finance must absorb.
Includes bibliographical references and index.
uaj 12/04/2015
Loan
Keywords: Corporations; Entreprises; Corporate financing; Financial decisions and planning; Capital budgeting and structure